Artificial Intelligence based Optimal Placement of Phasor Measurement Unit for Smart Grid - Poudel, Sushmita; Adhikari, Sujan (Himalayan Journal of Applied Science and Engineering, 2022)
A Phasor Measurement Unit (PMU) device ensures the stability, reliability, and proper visibility of critical areas of the power grid by providing a synchro phasor measurement of both voltage and current in real-time. Since it is not practical to place them at each branch of the system, the main concern lies in achieving entire network observability either by direct or indirect measurement through an optimal set of PMUs placed at the optimal location. This gives rise to the Optimal PMU Placement Problem (OPP). In this paper, OPP is solved by an optimization technique i.e., a Genetic Algorithm. The constraints that can greatly affect obtaining optimal solutions are reviewed and the effect of including Zero Injection Bus (ZIB) on the proposed method in solving OPP is studied. The algorithm is applied to IEEE-14 and IEEE-30 bus test systems for validation purposes. Since optimal sets of solutions are obtained from the proposed method, the solutions are ranked by the system observability redundancy index to find the best one. Further, a comparative analysis of the result is done with the depth first search algorithm and other widely used algorithms.